Foot Morphology and Running Gait Pattern between the Left and Right Limbs in Recreational Runners - Jing Wen Pan; Mei Yee Mavis Ho; Ray Ban Chuan Loh; Muhammad Nur Shahril Iskandar; Pui Wah Kong (Physical Activity and Health, 2023)
Previous studies generally selected one foot to classify participants into groups with different foot types and then analyzed the running or walking biomechanics for one limb. Such approach may have neglected the possible differences in foot morphology and gait between two limbs. This study aimed to compare the foot morphological characteristics and running kinematics of the lower extremities between the left and right limbs among a group of healthy, asymptomatic runners. Forty-four participants [20 females, 24 males; age 25.1 (6.5) years old; height 167.2 (7.0) cm; body mass 62.8 (8.1) kg] were recruited. Foot morphological characteristics were measured for both feet, and bilateral running kinematics were analyzed with 2D video analysis. No significant between-limb differences were found in the foot dimensions, hallux valgus (bunion) angle, or navicular drop (all p > 0.05). On the other hand, several kinematic variables were significantly different between the left and right limbs during running, including the peak foot eversion (p = 0.014), peak knee flexion (p = 0.002), and peak hip adduction (p < 0.001). The results indicate that runners with similar morphological characteristics between the left and right feet can display between-limb gait asymmetry during running. Researchers and practitioners should be aware of the potential between-limb asymmetry in running kinematics and foot morphology. Future studies should avoid arbitrarily analyzing one limb to represent a runner’s gait or foot morphology.